Genetic Variants in Cytosolic Phospholipase A2 Associated With Nonsteroidal Anti-Inflammatory Drug–Induced Acute Urticaria/Angioedema - Jurado-Escobar, Raquel; Doña, Inmaculada; Triano-Cornejo, José; Perkins, James R.; Pérez-Sánchez, Natalia; Testera-Montes, Almudena; Labella, Marina; Bartra, Joan; Laguna, José J.; Estravís, Miguel; Agúndez, José A. G.; Torres, María J.; et al. (Frontiers in Pharmacology, 2021)
Nonsteroidal anti-inflammatory drugs (NSAIDs) are among the main triggers of drug hypersensitivity reactions, probably due to their high consumption worldwide. The most frequent type of NSAID-hypersensitivity is NSAID-cross-hypersensitivity, in which patients react to NSAIDs from different chemical groups in the absence of a specific immunological response. The underlying mechanism of NSAID-cross-hypersensitivity has been linked to cyclooxygenase (COX)-1 inhibition causing an imbalance in the arachidonic acid (AA) pathway. Despite NSAID-induced acute urticaria/angioedema (NIUA) being the most frequent clinical phenotype, most studies have focused on NSAIDs-exacerbated respiratory disease. As NSAID-cross-hypersensitivity reactions are idiosyncratic, only appearing in some subjects, it is believed that individual susceptibility is under the influence of genetic factors. Although associations with polymorphisms in genes from the AA pathway have been described, no previous study has evaluated the potential role of cytosolic phospholipase A2 (cPLA2) variants. This enzyme catalyses the initial hydrolysis of membrane phospholipids to release AA, which can be subsequently metabolized into eicosanoids. Here we analysed for the first time the overall genetic variation in the cPLA2 gene (PLA2G4A) in NIUA patients. For this purpose, a set of tagging single nucleotide polymorphisms (tagSNPs) in PLA2G4A were selected using data from Europeans subjects in the 1000 Genomes Project, and genotyped with the iPlex Sequenom MassArray technology. Two independent populations, each comprising NIUA patients and NSAID-tolerant controls, were recruited in Spain, for the purposes of discovery and replication, comprising a total of 1128 individuals. Fifty-eight tagSNPs were successfully genotyped in the discovery cohort, of which four were significantly associated with NIUA after Bonferroni correction (rs2049963, rs2064471, rs12088010, and rs12746200). These polymorphisms were then genotyped in the replication cohort: rs2049963 was associated with increased risk for NIUA after Bonferroni correction under the dominant and additive models, whereas rs12088010 and rs12746200 were protective under these two inheritance models. Our results suggest a role for PLA2G4A polymorphisms in NIUA. However, further studies are required to replicate our findings, elucidate the mechanistic role, and evaluate the participation of PLA2G4A variants in other phenotypes induced by NSAID-cross-hypersensitivity.